Non-small cell lung cancer with MET amplification: review of epidemiology, associated disease characteristics, testing procedures, burden, and treatments - Yang, Mo; Mandal, Erin; Liu, Frank X.; O’Hara, Richard M.; Lesher, Beth; Sanborn, Rachel E. (Frontiers in Oncology, 2024)
Introduction Mesenchymal-epidermal transition factor gene amplification (METamp) is being investigated as a therapeutic target in advanced non-small cell lung cancer (NSCLC). We reviewed the epidemiology and disease characteristics associated with primary and secondary METamp, as well as the testing procedures used to identify METamp, in advanced NSCLC. Economic and humanistic burdens, and the practice patterns and treatments under investigation for METamp were also examined. Methods Embase and Medline (via ProQuest), ClinicalTrials.gov, and Cochrane Controlled Register of Trials (2015–2022) were systematically searched. Conference abstracts were searched via Embase and conference proceedings websites (2020–2022). The review focused on evidence from the United States; global evidence was included for identified evidence gaps. Results The median rate of primary METamp in NSCLC across the references was 4.8% (n=4 studies) and of secondary METamp (epidermal growth factor receptor [EGFR]-mutant NSCLC) was 15% (n=10). Next-generation sequencing (NGS; n=12) and/or fluorescence in situ hybridization (FISH; n=11) were most frequently used in real-world studies and FISH testing most frequently used in clinical trials (n=9/10). METamp definitions varied among clinical trials using ISH/FISH testing (MET to chromosome 7 centromere ratio of ≥1.8 to ≥3.0; or gene copy number [GCN] ≥5 to ≥10) and among trials using NGS (tissue testing: GCN ≥6; liquid biopsy: MET copy number ≥2.1 to >5). Limited to no data were identified on the economic and humanistic burdens, and real-world treatment of METamp NSCLC. Promising preliminary results from trials enrolling patients with EGFR-mutated, METamp advanced NSCLC progressing on an EGFR-tyrosine kinase inhibitor (TKI) were observed with MET-TKIs (i.e., tepotinib, savolitinib, and capmatinib) in combination with EGFR-TKIs (i.e., gefitinib and osimertinib). For metastatic NSCLC and high-level METamp, monotherapy with capmatinib, crizotinib, and tepotinib are recommended in the 2022 published NSCLC NCCN Guidelines. Conclusion Primary METamp occurs in approximately 5% of NSCLC cases, and secondary METamp in approximately 15% of cases previously treated with an EGFR inhibitor. Variability in testing methods (including ISH/FISH and NGS) and definitions were observed. Several treatments are promising in treating METamp NSCLC. Additional studies evaluating the clinical, economic, and humanistic burdens are needed.